Legal Protection for Persons with Disabilities as Victims of Sexual Violence (Study of Medan District Court Decision No. 1245/Pid.B/2023 Pn Mdn - Resia, Twina; Panjaitan, Budi Sastra (LEGAL BRIEF, 2024)
This research is a type of normative legal research with the aim of the research to find out how legal protection is for people with disabilities as victims of sexual violence and to find out whether in the Medan District Court Decision Number 1245/pid. b/2023 PN Mdn people with disabilities as witnesses and victims receive maximum legal protection. The results of the study indicate that people with disabilities have the right to legal protection from the criminal acts of sexual violence they experience, while the Medan District Court Decision Number 1245/Pid.B/2023/PN Mdn has not been maximized in providing legal protection for people with disabilities who are victims of such actions, one of which is the article used by the judge in sentencing the defendant is Article 12 of Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence, where through this article the Medan District Court judge did not consider the victim who was a person with intellectual disabilities at all because the article is an article that regulates criminal sanctions for sexual violence for victims who do not have physical limitations. In this case, the judge ignored the existence of Article 15 paragraph (1) letter (h) of Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence, which stipulates that for sexual harassment of persons with disabilities, the criminal sanction is increased by 1/3 of the main sentence